2013
DOI: 10.1080/01930826.2013.865386
|View full text |Cite
|
Sign up to set email alerts
|

When Data Curation Isn't: A Redefinition for Liberal Arts Universities

Abstract: Data curation is one way that libraries are extending traditional services to meet the changing needs of patrons. Requirements from research funders have placed increased pressure on grant recipients to create Data Management Plans and to securely store raw data. Research universities have stepped up to provide comprehensive data support services. Despite discrepancies in funding and staff, smaller institutions can similarly provide robust services by focusing on their strengths, such as interdepartmental coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 10 publications
(5 reference statements)
0
15
0
1
Order By: Relevance
“…In a study of 416 researchers across many disciplines at Virginia Tech, 15% of respondents struggled with "dealing with sensitive data, data transmission, and encryption" (Shen, 2016, p. 510). An excellent synopsis of the current state of data management is provided by Toups and Hughes (2013), who said that researchers "believe they are managing data well, but their research is not without management issues" (p. 227).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study of 416 researchers across many disciplines at Virginia Tech, 15% of respondents struggled with "dealing with sensitive data, data transmission, and encryption" (Shen, 2016, p. 510). An excellent synopsis of the current state of data management is provided by Toups and Hughes (2013), who said that researchers "believe they are managing data well, but their research is not without management issues" (p. 227).…”
Section: Literature Reviewmentioning
confidence: 99%
“…All academic libraries have a responsibility for collecting and curating datasets. (Toups and hughes (2013) 12 have suggested that small universities and institutions may also provide comprehensive RDM services by collaborating with other departments for data management and curation. The same has also been proposed by Latham and Poe (2012) 13 .…”
Section: Data Curationmentioning
confidence: 99%
“…They found that conversations with a nearby research university was a useful learning experience that gave them confidence in their own newly created data management decisions. Toups & Hughes (2013) published the process and outcomes of their small liberal arts university's foray into data curation. To assess the data needs of researchers at Trinity University, the librarians conducted focus groups composed of 10 faculty from diverse disciplines.…”
Section: Literature Reviewmentioning
confidence: 99%